Crisis Transmission : Evidence from the Debt, Tequila, and Asian Flu Crises - De Gregorio, José; Valdés, Rodrigo O. (Washington, DC: World Bank, 2014)
This article analyzes how external crises spread across countries. The authors analyze the behavior of four alternative crisis indicators in a sample of 20 countries during three well-known crises: the 1982 debt crisis, the 1994 Mexican crisis, and the 1997 Asian crisis. The objective is twofold: to revisit the transmission channels of crises, and to analyze whether capital controls, exchange rate flexibility, and debt maturity structure affect the extent of contagion. The results indicate that there is a strong neighborhood effect. Trade links and similarity in pre-crisis growth also explain (to a lesser extent) which countries suffer more contagion. Both debt composition and exchange rate flexibility to some extent limit contagion, whereas capital controls do not appear to curb it.